A broken system? Examining the perilous state of quality assurance in crime scene practice. Issue 5 (September 2021) - Chowdhury, Mehzeb
Highlights: Lack of research in crime scene quality assurance has disadvantaged the field. No unified understanding of competence or quality exists in crime scene practice. ISO standards alone are inadequate to address scene-specific quality assurance frailties. Organisational oversight models fail to ensure individual practitioner competence. Jurisdiction-wide policy implementation through compellability is the way forward. Abstract: Quality assurance in crime scene practice is an underdeveloped and underexamined field despite the cruciality attributed to scene work in achieving criminal justice goals. Formulation of robust strategies has been a shortcoming of oversight bodies, with a marked history of failure to address scene-specific requirements. This paper explores quality assurance mechanisms in the United Kingdom (UK) in order to uncover the longstanding status quo, and sustained challenges facing quality control regimes both on an organisational and personal level. Recommendations on a change in policy, implementation and philosophy are examined to assist with the formulation of effective quality assurance schemes in crime scene practice and align it closer to its laboratory counterparts.